Trends in time allocation: A cross-country analysis - J. Ignacio Gimenez-Nadal; Almudena Sevilla (Institute for the Study of Labor (IZA), 2012)
Using detailed time-use data for seven industrialized countries from the 1970s until today we document general decreases in men's market work coupled with increases in men's unpaid work and child care, and increases in women's paid work and child care coupled with decreases in unpaid work. We also find almost universal increases in the time devoted to watching television over this period, and uncover a widespread increase in leisure inequality in favor of lower educated adults. Trends in leisure inequality mirror the general increase in income and earnings inequality experienced in most countries over this period, especially after the mid-1980s. All these findings are consistent with previous results for the US. However, in contrast to the increases in leisure found for the US, we fail to find common trends in leisure time across countries over the period analyzed.
Keywords: D12; D13; J2; 330; time use survey; leisure inequality; Gesellschaft; Verhaltensökonomik; Arbeitszeit; Freizeit; Zeitverwendung; Welt